2018
DOI: 10.1039/c8ay01496e
|View full text |Cite
|
Sign up to set email alerts
|

An ion imprinted amino-functionalized mesoporous sorbent for the selective minicolumn preconcentration of cadmium ions and determination by GFAAS

Abstract: An amino-functionalized mesoporous sorbent with double imprinting of Cd(ii) and surfactant micelles was prepared via the sol–gel co-condensation method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
0
11
2
1
Order By: Relevance
“…2b), demonstrating that the obtained adsorption materials had highly porous structures with good pore connectivity. 21,22 The specic surface area, and pore diameters, and total pore volumes in IIP@RS samples were further calculated by Brunauer-Emmett-Teller and Barrett-Joyner-Halenda models, respectively. It was found that the specic surface area of IIP@RS obtained from the nitrogen isotherm was 458.7 m 2 g À1 with a total pore volume of 0.31 cm 3 g À1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2b), demonstrating that the obtained adsorption materials had highly porous structures with good pore connectivity. 21,22 The specic surface area, and pore diameters, and total pore volumes in IIP@RS samples were further calculated by Brunauer-Emmett-Teller and Barrett-Joyner-Halenda models, respectively. It was found that the specic surface area of IIP@RS obtained from the nitrogen isotherm was 458.7 m 2 g À1 with a total pore volume of 0.31 cm 3 g À1 .…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that the Cd( ii )-induced cavities during gel formation mainly attributed to the recognition behavior of IIP@RS toward Cd( ii ). 21,40 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As pH increases, adsorption increases mainly due to a combined effect of adsorption, electrostatic attraction (note the negative surface of silanol groups) and chelation via the deprotonation of the amino groups. 25,34…”
Section: Effect Of the Phmentioning
confidence: 99%
“…[30][31][32][33] In this regard our group has been devoted to studying SPE in ow-through systems holding an MC with ller materials (with and without II) in the last few years. 34,35 In this sense, different arrangements of ow systems using magnetic ller materials immobilized by the action of a permanent magnetic eld have been sporadically reported in the literature. Problems related to material bleeding or need for reloading between measurements discourage this approach.…”
Section: Introductionmentioning
confidence: 99%